2022
DOI: 10.17221/119/2021-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Validation of CAPS marker WR003 for the leaf rust resistance gene Lr1 and the molecular evolution of Lr1 in wheat

Abstract: The wheat leaf rust resistance gene Lr1 encodes a typical coiled-coil nucleotide-binding site leucine-rich repeat (CC-NBS-LRR) of resistance protein containing 1 344 amino acids. WR003, a cleaved amplified polymorphic sequence (CAPS) marker is derived from the LRR regions of Lr1. In this study, a worldwide collection of 120 Aegilops tauschii accessions and 282 hexaploid wheat varieties was screened for Lr1 alleles using WR003, and the specificity of WR003 for Lr1 was confirmed by pathogenicity tests and genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Haplotype-based functional markers (etc., CAPS) are more reliably and easily used for applied breeding because they are derived from SNPs within the target genes or their regulatory sequences and are more likely to be related to phenotype variations (Roso et al, 2010; Ravikiran et al, 2018; Rasheed and Xia, 2019; Liu et al, 2022). In hydroponic solutions, in our previous study, Hap3 of TaPHT1;9-4B were identified by CAPS-799 functional marker and speculated to be Pi-efficient wheat cultivars by evaluating the TaPHT1;9-4B expression levels, biomasses, and P contents (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Haplotype-based functional markers (etc., CAPS) are more reliably and easily used for applied breeding because they are derived from SNPs within the target genes or their regulatory sequences and are more likely to be related to phenotype variations (Roso et al, 2010; Ravikiran et al, 2018; Rasheed and Xia, 2019; Liu et al, 2022). In hydroponic solutions, in our previous study, Hap3 of TaPHT1;9-4B were identified by CAPS-799 functional marker and speculated to be Pi-efficient wheat cultivars by evaluating the TaPHT1;9-4B expression levels, biomasses, and P contents (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Changes. e wheat leaf rust resistance gene Lr1 produces a 1 344-amino-acid resistance protein with a characteristic coiled-coil nucleotide-binding site leucine-rich repeat (CC-NBS-LRR) [99]. Lr35-induced adult resistance to Puccinia triticina is mediated by the TaLr35PR5 gene [100].…”
Section: Different Lr Genes and Amino Acidsmentioning
confidence: 99%